CADETS’ PERCEPTION FOR MULTIMEDIA WEB-BASED LEARNING AND TECHONOLOGY ADVANCEMENT FOR MET IN STEM GOAL: CASE STUDY IN AKMI CIREBON FOR ON BOARD PREPARATION - Iing Mustain; yeyen Herlina (Jurnal Maritim Malahayati, 2023)
Teaching and learning for online learning has developed at the Maritime Academy of Suaka Bahari. Such the learning media which the Moodle application to prepare the cadet applied technological knowledge dan competence on the ship. Because of the seafarer competences have to be completed proficiently while they are learning in Maritime Education and Training (MET). Since the revolution industry 4.0 has emergence in the industry, the technological advancement required for workplace maritime competence. Such as integrating digital data, software, and information technologies. There for Maritime workplace has undergone rapid technological advancement. STEM qualification in the maritime industry careers for employers have increased related technological advances and mathematics for the marine, nautical science and marine engineering. Research design this study use the qualitative research A total of 41 cadets from deck officer and engineering officer Maritime Academy of Suaka Bahari have participated filling the questioners. This research founded that perceptions of the use of web-based multimedia in the Prala STEM application, on average, strongly agree at 53% in making it easier to understand the material. Meanwhile, 31.7% of cadets enthusiastically stated that they strongly agreed that they were not enthusiastic about using web-based multimedia in the Prala STEM application.